2013
DOI: 10.1128/jvi.01671-13
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 Inhibitor 17-DMAG Decreases Expression of Conserved Herpesvirus Protein Kinases and Reduces Virus Production in Epstein-Barr Virus-Infected Cells

Abstract: H uman herpesviruses are enveloped viruses containing relatively large, double-stranded DNA genomes. Although all herpesviruses experience both latent and lytic stages of infection, they are grouped into three separate families (alpha-, beta-, and gammaherpesviruses) according to differences in sequence homology and cellular tropisms. The alphaherpesviruses, which comprise herpes simplex virus 1 (HSV-1), HSV-2, and varicella-zoster virus (VZV), cause recurrent skin lesions and meningitis (1, 2). Human cytomega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 99 publications
2
32
0
Order By: Relevance
“…Moreover, it has been shown that Hsp90 and the PI3K/Akt pathway are critical for replication of CMV and survival of EBV-infected cells [79,80]. These findings further underscore our assumption that an anti-aGvHD strategy with combined Hsp90/PI3K/Akt inhibition might provide an additional protection against opportunistic infections and probably spare, for the most part, the GvI effect.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Moreover, it has been shown that Hsp90 and the PI3K/Akt pathway are critical for replication of CMV and survival of EBV-infected cells [79,80]. These findings further underscore our assumption that an anti-aGvHD strategy with combined Hsp90/PI3K/Akt inhibition might provide an additional protection against opportunistic infections and probably spare, for the most part, the GvI effect.…”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, it has been demonstrated that Hsp90 inhibitors have strong antifungal activity by preventing the emergence of resistance against echinocandin and azole drugs, 2 classes of antifungal drugs that are widely used for treatment against C. albicans and A. fumigatus infection [77,78]. Moreover, it has been shown that Hsp90 and the PI3K/Akt pathway are critical for replication of CMV and survival of EBV-infected cells [79,80]. These findings further underscore our assumption that an anti-aGvHD strategy with combined Hsp90/PI3K/Akt inhibition might provide an additional protection against opportunistic infections and probably spare, for the most part, the GvI effect.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression of the EBV-encoded and HCMV-encoded kinases is markedly decreased in EBV-infected and HCMV-infected cells, respectively, when treated with 17-DMAG. Furthermore, 17-DMAG reduces production in Epstein-Barr virus-infected cells (Sun et al, 2013). Based on the studies above, we can speculate that all four of the cellular genes identified in our study may play important roles during virus infection, and may impact virus replication directly or indirectly.…”
Section: Discussionmentioning
confidence: 88%
“…Other viral proteins such as the herpes simplex virus 1 (HSV-1) polymerase and Kaposi's sarcoma herpesvirus (KSHV) LANA have also been shown to be localized in the nucleus together with HSP90 (39,40). Indeed, there are an abundance of viral proteins that utilize HSP90 for proper folding, stabilization, and/or trafficking; thus, HSP90 inhibitors represent a potent new class of antiviral drugs with activity against a broad range of viruses, including influenza, hepatitis, and herpesviruses (63)(64)(65). Our results using chronically infected HTLV-1-producing cell lines and proviral clones indicate that HTLV-1 replication is also blocked by HSP90 inhibition.…”
Section: Discussionmentioning
confidence: 99%